Mathematical modelling of servo valve line hydraulic system - Jayaraman Vasanth Kumar (2013)
The electro hydraulic power transmissions are widely used in marine and offshore industries. Mathematical model was carried out for electro-hydraulic steering gear system. The effects of hydraulic system parametric variation on its stability and response were analysed. It will lead to a better understanding of the concept of hydraulic power systems design in marine engineering application.